Designing a Web-Based Company Profile Information System to Support Information Technology Governance in Event Organizers and Wedding Organizers - Intan Azizah; Devian Annas Tawadzu (Governance IT Adoption and Technology Advance, 2026)
Digital transformation requires business actors in the service sector, such as CV. Brother Indonesia, which is engaged in Event Organizer (EO) and Wedding Organizer (WO), to have a strong digital identity to increase credibility and market reach. So far, reliance on social media has caused the presentation of portfolio information and company profiles to be unstructured, making it difficult to access information for prospective clients of large institutions. This research aims to design and develop a professional web-based company profile information system as an integrated information media as well as a support tool for Information Technology (IT) governance. The development method used is the Waterfall model, which includes the stages of needs analysis, system design, implementation, and testing. The system is developed using the Laravel Framework and Tailwind CSS with interface design (UI/UX) designed through Figma. The results of the research resulted in an official digital platform that includes interactive portfolio features, communication contact integration, and an Admin Panel for content operational efficiency. Tests using the Black-Box method showed that the system ran stable and responsive on a variety of devices. The implementation of this website strategically supports the company's IT governance through the standardization of digital operational procedures that are more transparent, accountable, and aligned with long-term business goals.